Innovative particleboard material from the organic fraction of municipal solid waste. (December 2021) - Santos, Michael M.; Diez, Maria A.; Suárez, Marta; Centeno, Teresa A.
Abstract: This study presents a challenging approach that addresses the efficient management of the organic fraction of municipal solid waste (OFMSW) by hydrothermal carbonization (HTC) for the development of novel sustainable low-CO2 building materials. Mild HTC treatment at 180 °C for 2 h transformed low-grade OFMSW into a renewable carbonaceous solid (hydrochar), which displays promising properties for application in particleboards. Taking advantage of the presence of extractives acting as natural binders, the hydrochar particles with sizes of <0.3 mm, 0.3–1 mm, and 1–2 mm agglomerate successfully by simple pressing at 3 MPa for 7 min at room temperature (∼ 25 °C). The resulting binderless monolithic probes display a density of 838 and 883 kg/m 3 for the finest and coarsest grain sizes, respectively, and approximately 30% porosity. The mechanical resistance is enhanced by the use of larger particle sizes, and values of modulus of rupture and tensile strength of 21.64 MPa and 18.99 MPa are reached, respectively. The thermal conductivity of the probes in the range of 0.091–0.132 W/(m∙K) suggests the potential of OFMSW-derived hydrochar for thermal insulation panels. Graphical abstract: Image 1 Highlights: Food waste as precursor of novel sustainable low-CO2 building material. Hydrochar derived from food waste displays great prospects as particleboard material. Binderless hydrochar probes achieve density ∼ 850 kg/m 3 and 30% porosity. Binderless probes with MOR of 14–22 MPa and thermal conductivity of 0.091–0.132 W/(m∙K).